2015
DOI: 10.1037/tps0000029
|View full text |Cite
|
Sign up to set email alerts
|

Digesting antifat attitudes: Locus of control and social dominance orientation.

Abstract: Defined as the faulty assumptions about and general dislike of heavy individuals, antifat attitudes are pervasive and pose numerous consequences for the health of people who are overweight. Despite the continual rise of obesity rates in the United States, there is a paucity of research examining the underlying psychosocial factors associated with antifat attitudes. This study used hierarchical regression to examine the unique contributions of weight and health locus of control and social dominance orientation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Items include such statements as, "I have a hard time taking fat people too seriously," and respondents are asked to rate their agreement with the statements on a 0 to 9 Likert scale. The AAQ has been used among adult samples with overweight and obesity [32]. Internal consistency (Cronbach's alpha) in the present sample was 0.79 for the Dislike subscale, 0.82 for the Fear of Fat subscale and 0.64 for the Willpower subscale.…”
Section: Anti-fat Attitudes Questionnaire (Aaq)mentioning
confidence: 72%
“…Items include such statements as, "I have a hard time taking fat people too seriously," and respondents are asked to rate their agreement with the statements on a 0 to 9 Likert scale. The AAQ has been used among adult samples with overweight and obesity [32]. Internal consistency (Cronbach's alpha) in the present sample was 0.79 for the Dislike subscale, 0.82 for the Fear of Fat subscale and 0.64 for the Willpower subscale.…”
Section: Anti-fat Attitudes Questionnaire (Aaq)mentioning
confidence: 72%
“…Future research should also examine if and how individual characteristics of observers impact the impression formation process online in muscle talk contexts. For instance, the strength of weight stigma is influenced by such individual factors as one’s own weight status (Schwartz, Vartanian, Nosek, & Brownell, 2006) and weight locus of control, which refers to the degree to which individuals believe they have control over their weight (Elison & Çiftçi, 2015). Such individual factors might interact with not only the effect of body build but also the content of the comments.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, individuals high in social dominance orientation express greater social distance toward people with obesity (O'Brien, Latner, Ebneter, & Hunter, 2013). Recently, it has been confirmed that the relationship that exists between social dominance orientation and antifat attitudes (Elison & Çiftçi, 2015).…”
Section: Disgustmentioning
confidence: 97%